THE EFFECT OF THE BITCOIN VIRTUAL CURRENCY CHANGE ON THE ELECTRONIC TRADING MARKET - Mohammed Abdulkareem Ahmed, Ali Abdulqader Ahmed, AyadDakheelSaleem , Mohammed Ahmed Mustafa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The development that occurred in the electronic trading market is one of the main reasons that led to the emergence of new financial tools that help the user to conduct various operations such as buying and selling and other commercial operations. That is why we chose the Bitcoin currency as an example of this study, because it did not get much attention and focus of the world, as well as it is one of the most important new electronic financial currencies that have received great demand among users and came with specifications and advantages that were not available in many other electronic currencies. It is necessary to study new currencies and establish modern and integrated foundations and standards to help the emergence of integrated currencies in all respects and reduce the emergence of other currencies that do not possess the qualifications or specific criteria in order not to affect the markets when issuing a new currency and we will take bitcoin currency as a model for our study and its impact on the electronic trading market, which It is considered one of the important markets today because of the facilities and advantages it provides to customers..